Teaching French as a Foreign Language to Iranian Adult Learners: Problems and Solutions - Meibodi, Nazita Azimi; Gharaei, Zohreh (Mediterranean Journal of Social Sciences, 2012)
This article is a general overview on the problems that stand in the way of Iranian adult learners of French. The articleintroduces the linguistic background of learners as one of the factors causing problems for them. English, the language they learnt duringschool years, and Persian, their mother tongue, are introduced as the main sources of these problems and this is because of thedifferences they have with French. The problems are categorized into three categories of discriminating phonemes and segmentingwords, pronouncing and writing adjectives and finally pronouncing and writing verbs. Attempt has been made to offer some solutions forthe existing problems as well. Teaching phonemes meticulously from the very outset of training can be one of the solutions to thisproblem. As the next step, after acquiring some preliminary skills by learners, teachers should focus on some other aspects includingself correction and self monitoring exercises. They should also ask learners to record their voice and listen to it and to guess themeaning from context.